Systematic review and meta-analysis comparing low-flow duration of extracorporeal and conventional cardiopulmonary resuscitation - Mandigers, Loes; Boersma, Eric; den Uil, Corstiaan A; Gommers, Diederik; Bělohlávek, Jan; Belliato, Mirko; Lorusso, Roberto; Dos Reis Miranda, Dinis (Interactive cardiovascular and thoracic surgery, 2022)
OBJECTIVES: After cardiac arrest, a key factor determining survival outcomes is low-flow duration. Our aims were to determine the relation of survival and low-flow duration of extracorporeal cardiopulmonary resuscitation (ECPR) and conventional cardiopulmonary resuscitation (CCPR) and if these 2 therapies have different short-term survival curves in relation to low-flow duration. METHODS: We searched Embase, Medline, Web of Science and Google Scholar from inception up to April 2021. A linear mixed-effect model was used to describe the course of survival over time, based on study-specific and time-specific aggregated survival data. RESULTS: We included 42 observational studies reporting on 1689 ECPR and 375 751 CCPR procedures. Of the included studies, 25 included adults, 13 included children and 4 included both. In adults, survival curves decline rapidly over time (ECPR 37.2%, 29.8%, 23.8% and 19.1% versus CCPR-shockable 36.8%, 7.2%, 1.4% and 0.3% for 15, 30, 45 and 60 min low-flow, respectively). ECPR was associated with a statistically significant slower decline in survival than CCPR with initial shockable rhythms (CCPR-shockable). In children, survival curves decline rapidly over time (ECPR 43.6%, 41.7%, 39.8% and 38.0% versus CCPR-shockable 48.6%, 20.5%, 8.6% and 3.6% for 15, 30, 45 and 60 min low-flow, respectively). ECPR was associated with a statistically significant slower decline in survival than CCPR-shockable. CONCLUSIONS: The short-term survival of ECPR and CCPR-shockable patients both decline rapidly over time, in adults as well as in children. This decline of short-term survival in relation to low-flow duration in ECPR was slower than in conventional cardiopulmonary resuscitation. TRIAL REGISTRATION: Prospero: CRD42020212480, 2 October 2020.
Keywords: Heart Arrest; Survival; Cardiopulmonary resuscitation; srdeční zástava; Retrospective Studies; Time Factors; mimotělní membránová oxygenace; Cardiopulmonary Resuscitation; Extracorporeal cardiopulmonary resuscitation; Adult; dítě; Child; kardiopulmonální resuscitace; Heart arrest; retrospektivní studie; Extracorporeal Membrane Oxygenation; Humans; Cardiac arrest; Out-of-Hospital Cardiac Arrest; časové faktory; dospělí; zástava srdce mimo nemocnici; lidé